181k views
4 votes
Let f(x) = 5x - x+1 and g(x) = -3x. Evaluate the composition (f • g)(1).

Let f(x) = 5x - x+1 and g(x) = -3x. Evaluate the composition (f • g)(1).-example-1
User Renis
by
6.5k points

1 Answer

2 votes

Replace the variable x with 1 in the expression

f(1)=5(1)−(1)+1

f(1) = 5

Replace the variable x with 1 in the expression.

g(1)=−3⋅1

g(1) = -3

Multiply 5 by −3

.

−15⋅1

Multiply −15

by 1

.

−15

Thus, the answer is -15

I am unsure about this answer, I have doublechecked it several times. Please take this with a grain of salt